Function of isoamylase‐type starch debranching enzymes ISA1 and ISA2 in the Zea mays leaf. Issue 4 (19th August 2013) - Lin, Qiaohui; Facon, Maud; Putaux, Jean‐Luc; Dinges, Jason R.; Wattebled, Fabrice; D'Hulst, Christophe; Hennen‐Bierwagen, Tracie A.; Myers, Alan M.
Summary: Conserved isoamylase‐type starch debranching enzymes (ISAs), including the catalytic ISA1 and noncatalytic ISA2, are major starch biosynthesis determinants. Arabidopsis thaliana leaves require ISA1 and ISA2 for physiological function, whereas endosperm starch is near normal with only ISA1. ISA functions were characterized in maize ( Zea mays ) leaves to determine whether species‐specific distinctions in ISA1 primary structure, or metabolic differences in tissues, are responsible for the differing ISA2 requirement. Genetic methods provided lines lacking ISA1 or ISA2. Biochemical analyses characterized ISA activities in mutant tissues. Starch content, granule morphology, and amylopectin fine structure were determined. Three ISA activity forms were observed in leaves, two ISA1/ISA2 heteromultimers and one ISA1 homomultimer. ISA1 homomultimer activity existed in mutants lacking ISA2. Mutants without ISA2 differed in leaf starch content, granule morphology, and amylopectin structure compared with nonmutants or lines lacking both ISA1 and ISA2. The data imply that both the ISA1 homomultimer and ISA1/ISA2 heteromultimer function in the maize leaf. The ISA1 homomultimer is present and functions in the maize leaf. Evolutionary divergence between monocots and dicots probably explains the ability of ISA1 to function as a homomultimer in maize leaves, in contrast to other species where the ISA1/ISA2 heteromultimer is the only active form.